2010
DOI: 10.1097/id.0b013e3181f57288
|View full text |Cite
|
Sign up to set email alerts
|

Osteotome-Mediated Sinus Floor Elevation Using Only Platelet-Rich Fibrin: An Early Report on 110 Patients

Abstract: Early review of the OMSFE/PRF technique presented for localized sinus floor elevation and implant placement demonstrates a high degree of safety and success at sites with 5- to 8-mm residual subantral bone height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 28 publications
4
80
1
4
Order By: Relevance
“…Toffler et al. (2010) reported on 110 cases of osteotome‐mediated SFE, with L‐PRF as sole filling material during implant placement. The mean increase in the height at implant sites was 3–4 mm (range 2.5–5 mm), similar to the traditional osteotomes procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Toffler et al. (2010) reported on 110 cases of osteotome‐mediated SFE, with L‐PRF as sole filling material during implant placement. The mean increase in the height at implant sites was 3–4 mm (range 2.5–5 mm), similar to the traditional osteotomes procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[77][78][79] For this purpose, to obtain promising results from PRP in comparison with PRF, combination therapy should be used. Hence, strategies to improve the slow release of GF mechanisms, such as the new concentration of scaffold preparations and related studies, provide promising perspectives for future exploration.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…4) Radiological bone change was measured by examining the digital panoramic radiographs and CT images taken 18 reported high success rate of 97.8%. This study also showed similar success rate of 95.3%.…”
Section: Vertical Bone Gain After Hpise Surgery (Table 2)mentioning
confidence: 99%